Simulação de dinâmica molecular de um modelo de CAR em interação com o CD19, marcador de células cancerosas - Oliveira, Natália Fernandes Frota (2020)
Chimeric antigen receptors (CARs) consist of three components: an extracellular domain, a transmembrane domain, and an intracellular domain. These receptors can be introduced into human T cells to redirect antigen specificity and improve function in passive immunotherapy. The extracellular domain is the responsible for antigen recognition, which is usually formed by a single chain fragment variable (scFv); and a spacer (hinge). The main function of the transmembrane domain is to connect the extra and intracellular domains of CAR and, as well as the hinge, can influence the effector function of the CAR T cell. The intracellular domain is the activating portion of T cells, usually formed of CD3-ζ. Immunotherapy using anti-CD19 CAR-T cells is an effective treatment for leukemias and lymphomas affecting B cells. CD19 is expressed on malignant B cells and is therefore a potent marker of cancer cells. The objective was to obtain structural information, through molecular dynamics simulation, related to the signaling mechanism in a modeled CAR inserted in a T cell membrane model. The CAR components were modeled by Comparative Modeling and submitted to Molecular Dynamics (MD) simulations. The scFv, hinge, transmembrane and intracellular domain structures were joined to form the CAR and submitted to DM. DMs were conducted using the GROMACS package and the force field used to describe atomic interactions was CHARMM36. The distance, angle and PCA analyzes made it possible to infer the signal transduction mechanism in the CAR-CD19 system, which was not observed in the CAR system. The formation of the hinge-scFv interface and the approximation of this assembly to the membrane results in a reduction of the tension in the hinge-transmembrane binding region, which allows the α-helix bias of the transmembrane domain. This inclination lasts from 370 ns to ~ 600 ns, at which time a conformational change in the intracellular domain is observed, ratified by the rapid transition observed on the PC1 curve at 600 ns. This sequence of events proposes a signal transduction mechanism in the CAR T cell, dependent on the interaction between CD19 and scFv until the conformational change of the intracellular domain, providing CD3-iros tyrosine residues for phosphorylation and signal transmission inside. of the CAR T cell. The movements leading to sequential conformational changes in CAR-CD19 are in agreement with the CAR function described in the literature. The proposed mechanism ratifies conformational changes in the intracellular domain that is essential for exposing phosphorylation sites and the function of CD3-ζ, which plays a role in signaling.